How to Move from Agile to Agility in Software Organizations - Albera , Sumia Ali; Abdalhamid, Samia A.; Abd Aljalil, Asma M. (Al-Mukhtar Journal of Sciences, 2023)
Agility adoption in software development organizations is considered a strong solution to managing a rapidly changing, uncertain, and unsteady workplace. Especially, as the objective of Agility is to control changes that may happen. So, moving from Agile to Agility increases the organizations’ ability in swiftly and effectively react to unexpected variations in market requests. Agile refers to a mindset emphasizing teamwork, frequent value delivery, and the ability to deal with functional changes. The distinction between Agile and Agility needs to be understood in order to prevent misunderstandings, because Agility is recognized as one of the most important attributes of an organization against market turbulence. Through systematic mapping, this research explores the transition from Agile to Agility in software development companies. Systematic mapping is a technique for gathering, collating, and presenting research evidence. Eight research questions were identified, and to provide answers to these questions, several research papers have been explored in electronic databases. Eventually, 33 research papers were inspected, and answers to all research questions were provided. The results that have been achieved by this research proved that Agile and Agility differ in terms of definitions, attributes, numbers of dimensions, and the dimensions themselves